Magnetic tracking of eye position in freely behaving chickens - Schwarz, Jason S.; Sridharan, Devarajan; Knudsen, Eric I. (Frontiers in Systems Neuroscience, 2013)
Research on the visual system of non-primates, such as birds and rodents, is increasing. Evidence that neural responses can differ dramatically between head-immobilized and freely behaving animals underlines the importance of studying visual processing in ethologically relevant contexts. In order to systematically study visual responses in freely behaving animals, an unobtrusive system for monitoring eye-in-orbit position in real time is essential. We describe a novel system for monitoring eye position that utilizes a head-mounted magnetic displacement sensor coupled with an eye-implanted magnet. This system is small, lightweight, and offers high temporal and spatial resolution in real time. We use the system to demonstrate the stability of the eye and the stereotypy of eye position during two different behavioral tasks in chickens. This approach offers a viable alternative to search coil and optical eye tracking techniques for high resolution tracking of eye-in-orbit positions in behaving animals.